Clinical effects of prior trastuzumab on combination eribulin mesylate plus trastuzumab as first-line treatment for human epidermal growth factor receptor 2 positive locally recurrent or metastatic breast cancer: results from a Phase II, single-arm, multicenter study - Puhalla, Shannon (Breast Cancer (Dove Med Press), 2016)
Eribulin mesylate, a novel nontaxane microtubule dynamics inhibitor in the halichondrin class of antineoplastic drugs, is indicated for the treatment of patients with metastatic breast cancer who previously received ≥2 chemotherapy regimens in the metastatic setting. Primary data from a Phase II trial for the first-line combination of eribulin plus trastuzumab in human epidermal growth factor receptor 2 positive patients showed a 71% objective response rate and tolerability consistent with the known profile of these agents. Here, we present prespecified analyses of efficacy of this combination based on prior trastuzumab use. Patients received eribulin mesylate 1.4 mg/m(2) (equivalent to 1.23 mg/m(2) eribulin [expressed as free base]) intravenously on days 1 and 8 plus trastuzumab (8 mg/kg intravenously/cycle 1, then 6 mg/kg) on day 1 of each 21-day cycle. Objective response rates, progression-free survival, and tolerability were assessed in patients who had and had not received prior adjuvant or neoadjuvant (neo/adjuvant) trastuzumab treatment. Fifty-two patients (median age: 59.5 years) received eribulin/trastuzumab for a median treatment duration of ~31 weeks; 40.4% (n=21) had been previously treated with neo/adjuvant trastuzumab prior to treatment with eribulin plus trastuzumab for metastatic disease (median time between neo/adjuvant and study treatment: 23 months). In trastuzumab-naïve patients (n=31) compared with those who had received prior trastuzumab, objective response rate was 77.4% versus 61.9%, respectively; duration of response was 11.8 versus 9.5 months, respectively; clinical benefit rate was 87.1% versus 81.0%, respectively; and median progression-free survival was 12.2 versus 11.5 months, respectively. The most common grade 3/4 treatment-emergent adverse events (occuring in ≥5% of patients) in patients who received prior trastuzumab versus trastuzumab naïve patients, respectively, were neutropenia (47.6% vs 32.3%), peripheral neuropathy (14.3% vs 25.8%), febrile neutropenia (14.3% vs 3.2%), fatigue (9.5% vs 6.5%), nausea (9.5% vs 0%), vomiting (9.5% vs 3.2%), and leukopenia (9.5% vs 3.2%). In patients with human epidermal growth factor receptor 2 positive metastatic breast cancer, first-line eribulin/trastuzumab treatment demonstrated substantial antitumor activity and was well tolerated, regardless of prior neo/adjuvant trastuzumab treatment.